Behaviour and design of rubberised concrete filled steel tubes under combined loading conditions. (June 2019) - Dong, Minhao; Elchalakani, Mohamed; Karrech, Ali; Hassanein, Mostafa Fahmi; Xie, Tianyu; Yang, Bo
Abstract: Rubberised concrete has the benefit of utilising waste material, preventing resource extraction and improving concrete ductility, however at the cost of reduced strength and stiffness. This paper explored the option to effectively confine the rubberised concrete with steel tubes to obtain enhanced strength and ductility. The behaviour and performances of thirty rubberised concrete-filled single-skin steel tubes of various rubber content, steel section and load eccentricities was systematically investigated in this study. The results have shown that confined rubberised concrete and the restrained steel tube improved ductility of the composite section. The rubberised concrete was more effective in delaying the premature buckling failure of the steel tube compared to the more brittle normal cement concrete. The 15% rubber replacement ratio showed a good balance of strength and ductility and thus recommended for design of roadside barriers. The behaviour of the rubberised concrete filled steel tubes could be accurately predicted using existing design guidelines and safe designs can be produced. This study demonstrated the possibility of using rubberised concrete as a solution to problems that require high moment and deformation capacity, such as the roadside barriers and columns in buildings located in seismic active zones. Highlights: The strength deficiency of the rubberised concrete could be mitigated by steel confinement. The rubberised concrete infill could effectively delay the fracture of the steel tubes. The slenderer steel sections experienced greater ductility improvements with concrete infill. The interaction diagrams of RuCFST could be accurately predicted using existing codes.